Víctima del delito y víctima de la discriminación: la relevancia de la víctima en la circunstancia agravante del art. 22.4ª del Código Penal - Doval Pais, Antonio (Revista de victimología, 2024)
The commission of an offence on discriminatory grounds constitutes an aggravating circumstance of criminal liability under Spanish criminal law. Generally, in practice, the characteristics that are the object of the agent’s aversion are found in the victim of the attack herself, but sometimes the offence affects persons without these characteristics, either alone or as part of a group including the person with the discrimination feature. The amendment of art. 22.4 of the Penal Code in 2021 has brought a new and important element to the question of the scope of this precept with respect to these cases: the irrelevance of ‘such conditions or circumstances actually being present in the person on whom the conduct falls’. However, despite the addition of this new clause, the law continues to require that the characteristics reside in the victim. The aim of this paper is to study the scope of applicability of the article in different possible cases with particular respect to the victims, with special emphasis on the relationship between the answers and the reason for the aggravating circumstance.